2017
DOI: 10.1021/acs.analchem.7b03571
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Two-Dimensional 1H, 13C Methyl NMR Spectra of Monoclonal Antibody Therapeutics To Facilitate Assessment of Higher Order Structure

Abstract: Two-dimensional (2D) 1H-13C methyl NMR provides a powerful tool to probe the higher order structure (HOS) of monoclonal antibodies (mAbs), since spectra can readily be acquired on intact mAbs at natural isotopic abundance, and small changes in chemical environment and structure give rise to observable changes in corresponding spectra, which can be interpreted at atomic resolution. This makes it possible to apply 2D NMR spectral fingerprinting approaches directly to drug products in order to systematically char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 28 publications
1
58
0
1
Order By: Relevance
“…To determine if glycosylation is responsible for the slower migration of the NISTmAb heavy chain, an aglycosylated form of the NISTmAb was generated using PNGase F as previously described. 21 As shown in Figure 2, the migration of the eNISTmAb heavy chain is similar to the aglycosylated form of the NISTmAb heavy chain (Figure 2, compare lane 3 to lane 2), suggesting that the faster migration of the eNISTmAb heavy chain is due to the lack of glycosylation. Subsequent mass spectral analysis confirmed that the intact masses of the heavy and light chains matched the theoretical masses.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…To determine if glycosylation is responsible for the slower migration of the NISTmAb heavy chain, an aglycosylated form of the NISTmAb was generated using PNGase F as previously described. 21 As shown in Figure 2, the migration of the eNISTmAb heavy chain is similar to the aglycosylated form of the NISTmAb heavy chain (Figure 2, compare lane 3 to lane 2), suggesting that the faster migration of the eNISTmAb heavy chain is due to the lack of glycosylation. Subsequent mass spectral analysis confirmed that the intact masses of the heavy and light chains matched the theoretical masses.…”
Section: Resultsmentioning
confidence: 71%
“…21,2936 The appropriate 2D-NMR method was applied to each eNISTmAb sample, e.g ., 1 H, 13 C constant time (CT) heteronuclear single quantum coherence spectroscopy (HSQC) for the U- 13 C sample; 1 H, 15 N gradient-selected (g)HSQC for the U- 15 N sample, and both methods for the triply-labeled 2 H, 13 C, 15 N sample (Figure 6, Fig. S6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together 1D and 2D NMR profiling methods offer a way to quantify spectral/structural differences between similar proteins, but more information is often needed to capture complicated solution behavior. One example, highlighted in Figure , is for a fast‐acting insulin analogue.…”
Section: Figurementioning
confidence: 99%
“…Ongoing efforts are focused on validating the diffusion profile interpretation of protein behavior by using orthogonal biophysical methods and combining the diffusion profile with NMR‐relaxation measurements to better relate the observed behavior to changes in both structure and dynamics. The diffusion profile shows promise as another 1 H NMR‐based profiling method that can easily be applied to study interactions and higher‐order structure and as a useful addition to the 1D PROFILE and 2D fingerprint methods, as a way to interpret observed changes in NMR spectra in terms of the solution behavior of the protein. All of these methods fit together in various aspects of discovery and development: they can be used to investigate the intrinsic behavior of the protein itself as well as subtle differences or changes in its behavior in formulation.…”
Section: Figurementioning
confidence: 99%